Reactions and Attitudes towards the Darul Arqam Movement in Southeast Asia - J.H. Meuleman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
This article discusses the various reactions and attitudes towards Darul Arqam in Southeast Asia, especially in mid-1994, when Darl Arqam became the object of heated debate between institutions and leaders who support the crackdown on Darul Arqam and who reject the action throughout the region. Within this context, the authors analyze the different establishments of various governments, religious organizations, other agencies and the general population in Malaysia, Indonesia, Thailand, and Singapore. The results of this analysis is not limited to the Darul Arqam issue alone, but showed various common traits of Islam in a number of regions and countries in Southeast Asia.DOI: 10.15408/sdi.v3i1.813